Research Progress on Iodine Capture by Covalent Organic Framework Materials - Zhang, Yeru (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the development of nuclear power, the removal of radionuclides is an important responsibility and task. Radioactive iodine, as one of the most radionuclide in nuclear wastes, its safe disposal is essential to ensure the sustainable development of the nuclear industry. Covalent organic framework materials are crystalline organic porous materials, which were constructed by covalent bonds. Because of their regular pore structure, large surface area and high chemical stability, covalent organic framework materials are selected as an ideal iodine capturing materials due to their structural characteristics and the adsorption sites of covalent organic framework materials. In this paper, the research progress of covalent organic framework materials in iodine capture was briefly reviewed. Meanwhile, the prospect of high efficiency iodine-capture covalent organic framework materials on industrialized application is predicted.